Optimization of video steganography with additional compression and encryption - Dwi Arraziqi; Endi Sailul Haq (Universitas Ahmad Dahlan, 2019)
Currently, data such as text, images and video are very important. Therefore, data must be secured from unauthorized parties. In this paper, we propose a number of security levels, first using compression techniques on the data that will be hidden to reduce the size of the data, second using encryption techniques on data that has been compressed so that data is more secure, third using video steganography techniques on compressed and encrypted data so that unauthorized parties are increasingly difficult to extract data. Measurement of differences in quality of cover-video and stego-video using MSE (Mean Square Error), PSNR (Peak Signal to Noise Ratio), evolution histogram of video tags, and video playback. The results show that the proposed algorithm gives better results than the previous algorithm which has a smaller MSE, larger PSNR, smaller histogram evolution of video tags, and play video without distortion.